Antipodean Aftershocks: Group Settlement of Hebridean and non-Hebridean Britons in Western Australia following World War One. Issue 2 (November 2020) - Jones, Roy; Jones, Tod
Abstract : In the speech in which the phrase 'land fit for heroes' was coined, Lloyd George proclaimed '(l)et us make victory the motive power to link the old land up in such measure that it will be nearer the sunshine than ever before … it will lift those who have been living in the dark places to a plateau where they will get the rays of the sun'. This speech conflated the issues of the 'debt of honour' and the provision of land to those who had served. These ideals had ramifications throughout the British Empire. Here we proffer two Antipodean examples: the national Soldier Settlement Scheme in New Zealand and the Imperial Group Settlement of British migrants in Western Australia and, specifically, the fate and the legacy of a Group of Gaelic speaking Outer Hebrideans who relocated to a site which is now in the outer fringes of metropolitan Perth.